Kesiapan dalam Menghadapi Bisnis Global: Studi Kasus Kopi Kenangan Gatot Subroto Kota Medan - Risya Nabila Fitri; Tsaqifa Aziza Siregar; Andini Rahayu Putri; Jones Wahyu Simamora; Dionisius Sihombing; Fadli Agus Triansyah (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
Globalization requires Micro, Small and Medium Enterprises (MSMEs) in Indonesia to increase their competitiveness in order to be able to compete in international markets. In this context, research was conducted to analyze the level of readiness of MSMEs to face global business challenges by taking a case study of Kopi Kenangan Gatot Subroto in Medan City. The research uses a qualitative method with a structured interview approach to management and employees, which includes aspects of internal readiness, expansion strategy, operational constraints, market opportunities, use of digitalization, as well as external support from the government and business partners. The research results show that Kopi Kenangan has a high level of readiness to face the global market through the implementation of consistent product quality standards, a mature expansion strategy, and adaptation to developments in digital technology. Apart from that, brand strength, consumer loyalty and collaboration with strategic partners are also important factors that strengthen a company's competitiveness. However, challenges such as changes in global consumer tastes, cultural differences, and increasing international competition are still obstacles that need to be anticipated. Overall, this research confirms that readiness for global business requires continuous innovation, strengthening the quality of human resources, and the application of international standards that are adaptive to technological developments.